Pengaruh Fintech Terhadap Kinerja Keuangan Umkm Dengan Literasi Keuangan Sebagai Variabel Moderasi - Ni Putu Rika Puspa Astari; Ica Rika Candraningrat (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
This study aims to examine the role of financial literacy in moderating the effect of fintech to financial performance. Quantitaive approach and primary data are used in this research. The primary data is obtained from questionare. The sampling method is quota sampling. Sample consist of 60 Balinese Culinary SMEs in Sarbagita area which then divided into 15 samples for each area such as Denpasar, Badung, Gianyar and Tabanan. Furthermore, data is analyzed using multivariate analysis named SEM PLS. The result shows that fintech has a positif and significant effect to financial performace. Another result shows that financial literacy can moderate (strengthen) the positif effect of fintech to financial performance. These results support the planned behavior and financial innovation theory. SMEs owners with high financial literacy rate can optimaly use the effectiveness of fintech in order to increase their financial performance